Using space - Roos, Alexander (My University, 2024)
This thesis takes place in a speculative scenario where the public ownership and rights to use the building of Skeppsbron 4 in central Gothenburg are recognised. Inspired by the past movement of allaktivitetshus and theories of alternative economies of use value. The mostly vacant building with an otherwise uncertain future is saved by a contract, opening up the building in trade of maintenance responsibility. By using an architectural office as a platform and mediator between the building and the public, shaping the building and organising a schedule of active tasks and free passive phases, the role of the architect is extended and tested. Establishing a relationship with the owners, makes it possible to be close to an existing building. Testing scenarios, configurate and constructing structures at site, using available materials, models and drawings. Based on the principles of simple machines as tools, to achieve a flexible layout to accommodate different scenarios in the limited space. This method becomes site specific but develops a potential strategy viable to other buildings. Skeppsbron 4s found state is reconfigured to fit specifically designed simple machines with various functions of different scales, while the existing structure is used as is in other cases. The interventions range from a wedge to signal access to the public, to a manually powered freight elevator connecting the floors. The simple machines are used as tools to interact with the building and shape it after need, creating a place where people can go to celebrate a birthday party or just escape the rain for some time. The thesis has provided an experience of being close to an existing building, constructing and testing scenarios in combination of real and speculative aspects, thru models as tools. With the approach that architecture is more than something to look at, but can be accessed and used as a resource from a public perspective.
Keywords: access, maintenance, simple machines